Digital infographics: The journalistic genre that emerged from trauma to foreshadow the course of a new visual culture for the media - Duarte, Assunção Gonçalves (Media & Jornalismo, 2021)
For most journalists and infographic designers, the 11 September Attacks in the USA are the pivotal moment for the emergence of digital infographics as a journalistic genre in the beginning of the 21st century. This article reflects on the circumstances of this moment and seeks to identify its impact on the evolution of infographics, journalism and audiences, all newly arrived in the digital world. For this paper, we analysed a short period in the recent history of digital journalism (2001-2002), which portraits a common history between Western world countries, including Portugal. This investigation come from a broader research project (PTDC/COM-JOR/28144/2017), which aims to draw the history of Portuguese Digital Infographics in the first two decades of this century, and also shares its scientific method: content analysis of digital infographics examples identified in two events that reward the genre (Obciber and Malofiej), digital infographics analysis outside the event when produced by the newspapers considered as the most innovative in the digital environment at the time, and interviews with Portuguese infographic designers and online editors who witnessed the genre evolution. This paper focuses on 5 digital infographics reporting the September 11 Attacks events. They were created between 2001 and 2002 by two of the most awarded newspapers in Malofiej awards for the early years of digital infographics: elmundo.es and the nytimes.com. To represent portuguese reality, it was chosen a digital infographic published by the first portuguese newspaper that introduced the genre in its online version: publico.pt. The results of this investigation highlight the birth of journalistic digital infographics framework — under the pressure of the first traumatic event of global repercussions in the Internet Era — as the definition engine which deeply marked itself in the history of the first experiences producing original visual content for the web, inside and outside journalism. These circumstances set the synergies that later paved the way for the rise of multimedia, cross-media and transmedia forms in visual digital narratives for journalism and are a clear testimony to a process of history mediatization that, for the first time, placed the internet side by side with the usual main actors (Tv, radio and newspapers). It was the emotional and political impact in a global scale of the September 11 Attacks that made journalists and audiences recognize the web as a fully-fledged informative social communication medium. Infographics in its digital version — dynamic and interactive — was the privileged agent of this recognition, ensuring to itself, albeit temporarily, the flagship role for a journalism in search of its main role in the new medium.